Food Policy in Bangladesh : A disaggregated model for stabilization f rice prices in Bangladesh - Shahabuddin, Quazi; Seminar on Evolving Food Markets and Food Policy in Bangladesh (1994 : Dhaka, Bangladesh) (Washington, D. C. International Food Policy Research Institute, 1991)
Contains keynote paper presented in session 1, and abstracts of papers presented at the seminar in sessions 1-11.
Cover title.
Microfiche.
Keywords: Food supply -- Bangladesh -- Congresses; Food policy -- Bangladesh -- Congresses